Elazı? başyurt earthquake: Experiences on the earthquake - Yildiz, Mustafa; Gurger, Mehtap; Sahan, Mustafa; Gulacti, Umut; Gundogdu, Tamer; Bozdemir, Mehmet Nuri; Goktekin, Mehmet Cagri (Drunpp-Sarajevo, 2012)
Objective: An earthquake of 6.0 on the Richter Scale hit the village of Başyurt in Elazi{dotless}? Province, Eastern Turkey on March 8, 2010. The epicenter was between Başyurt and Kovanci{dotless}lar. Methods: We reviewed retrospectively all the injuries related to the earthquake using the medical records. We recorded patients' demographic data, their complaints, injury types and outcomes. Results: During the study period, 74 patients presented to our emergency unit with injuries related to the earthquake. The mean age of these patients was 38.6 years (age range 0-110) and 39 of them were female. The most frequent injury occurrences were observed in the extremities (48.7%). 28 (%38.8) patients were trapped under debris. A total of 137 patients were injured and 42 patients died. Approximately 74 patients were transferred to the hospital within the first 24 hours after the incident. The rate of hospitalization was reported as 55% (74/41 patients). Conclusion: In conclusion, rescue teams and medical teams should be prepared and buildings should be constructed in accordance with earthquake regulations. Patients should receive proper fluid treatment.
Keywords: Earthquake; Emergency unit; Epidemiology